Theological-Applicative Implications Of The Concept Of Creation - Yonathan Salmon Efrayim Ngesthi; Godikay Sandeep (Jurnal Teologi (JUTEOLOG), 2022)
The doctrine of creation has become a focal point of debate between modern science and theologians. Thus we see that in today's developments, biblical theology has been confronted with theories that reject the historical and scientific value of the book of Genesis. Using descriptive qualitative methods, with a literature study approach, it can be concluded that evolutionism is contrary to the teachings of the Bible, it is based on the first, that there is no strong exegetical basis to make room for the evolutionary assumption that there is a measurable span of time in the process of creating the universe Second, the Bible's statement "In the beginning God created the heavens and the earth" ... within six days "(Genesis 1: 1, Exodus 20:20) is an indisputable biblical fact as an act of omnipotence and the majesty of God created the world from nothing. came into being by His word. Third, the doctrine of creation must be the foundation of Christian faith which is tested in the authority of the powerful Word of God (2 Tim. 3:16) and the world created by God and everything in it becomes an arena for scientific activity in the trajectory of human history that must be based on the Bible. Fourth, the creation statement Genesis 1: 1 is a refutation of various scientific theories and human philosophical views that contradict Bible truth (Gen. 1-2, Ps. 33: 4-9).